Selective lymph node dissection in early-stage non-small cell lung cancer - Han, Han; Chen, Haiquan (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
Lymph node dissection is a vital part of surgical treatment in early-stage non-small cell lung cancer (NSCLC). Removal of metastatic lymph nodes while preservation of intact lymph nodes are equally important. For hospitalized early-stage patients with limited lymph node metastasis, the operation treatment should be made according to some rules such as lobe-specific lymph node drainage pattern. In order to prevent unnecessary surgical trauma in early-stage patients, a minimally invasive approach with selective lymph node excision is preferred for more clinical benefits. This review summarizes the existing findings on lobe-specific lymph node drainage pattern and we hope to provide guidance for selective lymph node dissection (SLND). Furthermore, we include information on histologic views, a tumor marker and protocols of SLND, with hope to inspire creative research and clinical trials in this field.